Analysis of the in-hospital mortality in the tertiary referral department of neonatology and neonatal intensive care - Aleksander Kamianowski; Cezary Kamianowski; Gabriela Szpica; Angelika Jakubas; Anna Wasilewska; Monika Kamianowska (Scientific Reports)
Abstract Reducing neonatal mortality is a crucial part of health-care programs. We wanted to analyze the in-hospital mortality in the tertiary referral Department of Neonatology and Neonatal Intensive Care of the Medical University of Bialystok. The study was conducted on data of all neonates admitted to the Department between 2015 and 2023 (N = 19 171). During the study period the in-hospital mortality rate was 5.16 per 1000 live births and it was the highest in 2021 (8.15 per 1000 live births, p < 0.05). The leading underlying cause of death was extreme prematurity. 43.75% of the extremely preterm or extremely low birth weight neonates had a congenital/hospital acquired infection and 54.69% were not administered a full course of recommended antenatal corticosteroids. The in-hospital mortality rate in the Department was significantly higher than in Poland and other European countries due to the characteristics of the tertiary care Department and was generated mainly by deaths of premature neonates. It was the highest during the period of strict epidemiological restrictions related to the COVD-19 pandemic. Without detailed analyses of neonatal deaths in individual health care facilities and implementation of procedures to improve quality of care, it will not be possible to reduce the number of neonatal deaths.